Ayurvedic And Modern Concept of Granthi (Cyst) and Arbuda (Cancer) -A Review - Panwar, Neeraj; Gupta, Rajesh Kumar (International Research Journal of Ayurveda & Yoga, 2022)
One of our society’s most pressing issues these days is lifestyle disorders. Such diseases are primarily caused by an improper diet, poor eating habits, a lack of physical activity, and so on. When cells grow and divide more than they should or do not die when they should, an abnormal mass of tissue arises. Tumors are classified as either benign (non-cancerous) or malignant (cancerous) (cancer). Benign tumours can grow to be fairly large, but they do not spread to other parts of the body or surrounding tissues. Tumors that are malignant have the ability to infiltrate or disseminate into adjacent tissues. They can also spread through the blood and lymph systems to other regions of the body. Also known as neoplasm. It has become the most serious and well-known lifestyle disease in the world. Lifestyle disorders are diseases induced by Viruddha "Ahara" and "Vihara" in Ayurveda (food and regimen). Ayurveda is seen as a step forward in the treatment of tumours that are similar to the Sushrutha Samhita’s clinical entities of Arbuda and Granthi. The goal of this paper is to give an Ayurvedic and Modern conceptual study of Granthi and Arbuda.